Ensacamento de cachos de tomate visando ao controle das brocas-dos-frutos - Borges, Raoni Terra de Oliveira (2018)
Tomato cultivation is challenging due to high susceptibility to various pests and diseases. Fruit borer insects make fruits unfeasible for commercialization, besides favoring colonization by pathogens. The losses caused by borers can be avoided by bagging the bunches of fruits. The use of bags can be combined with conventional crop in order to obtain more sustainable and healthy results. Bagging can reduce the use of pesticides and its chemical remainings in fruits. This practice may also improve the quality of life of rural workers, since it can reduce their exposure to agrochemicals and correlated poisoning problems. The general effect of these measures are better quality and certainly more profitable products. The objective of this study was to evaluate the efficiency of tomato bagging in the control of fruit borer insects, its effects on lycopene content, taste, productivity and profitability. The experiment was conducted at field in the municipality of Uberaba-MG, from November 2016 to September 2017. The experimental design was a randomized block design, in a 3 x 5 factorial, with four replications. The factors consisted of three tomato hybrids: Dominador (salad), Ravena (Italian) and Carina Star (Santa Cruz), and fruit bagging types, made of NWT (non-woven tissue), tulle, organza, brown craft and a control factor,without fruit bagging. The decision of bagging use depends on the pest incidence in the area and the change in the agronomic characteristics of the tomato. The organza and tulle fruits bagging reduce the incidence of borer insects, relative to the control, in the cultivation in spring-summer. The dominador presents higher brix content among the evaluated hybrids. Carina Star, when bagged with organza, produces the fruits with higher levels of lycopene, being 116% superior to the other cultivars. From the second harvest, organza fabric is the most profitable bagging, since it is the only one that allows to be reused several times, being therefore more sustainable.